PRINCÍPIO ADITIVO E MULTIPLICATIVO: EXPLORANDO O PENSAMENTO COMBINATÓRIO POR MEIO DA RESOLUÇÃO DE PROBLEMAS E COM USO DE MATERIAIS MANIPULÁVEIS E JOGOS - Tolio, Francisca Brum (2016)
This research had as the mainly purpose to investigate the contributions of the Problems Solving Methodology and the use of games and manipulable materials can propitiate to the Additive Principle and Multiplicative Principle teaching and learning to high school students. To the development of this study, it was used the Solving Problems teaching-learning methodology suggested by the authors Alevatto and Onuchic. The manipulable materials and the games helped in the subject development turning it more understandable to the students and motivating them to solve the problems. The research was accomplished with a third year group of the Secondary Technical School from Instituto Federal de Educação, Ciência e Tecnologia Farroupilha – Câmpus Alegrete. The data collection was done by the participant observation, from the teacher’s registration in her dairy and the students registration of this activities development. Concluding this research, it was observed that the students were able to create their own concepts related to the addressed subjects, in such a way to differentiate the studied principles and apply them correctly when it’s necessary. It was also observed an improvement in the data reading comprehension. It can be inferred that this research development contributed significantly to the concepts building according to the additive and multiplicative principles.